Strengthening the health system as a strategy to achieving a universal health coverage in underprivileged communities in Africa: a scoping review - Jaca, A; Malinga, T; Iwu-Jaja, CJ; Nnaji, CA; Okeibunor, JC; Kamuya, D; Wiysonge, CS (MDPI, 2022)
Universal health coverage (UHC) is defined as people having access to quality healthcare services (e.g., treatment, rehabilitation, and palliative care) they need, irrespective of their financial status. Access to quality healthcare services continues to be a challenge for many people in low- and middle-income countries (LMICs). The aim of this study was to conduct a scoping review to map out the health system strengthening strategies that can be used to attain universal health coverage in Africa. We conducted a scoping review and qualitatively synthesized existing evidence from studies carried out in Africa. We included studies that reported interventions to strengthen the health system, e.g., financial support, increasing work force, improving leadership capacity in health facilities, and developing and upgrading infrastructure of primary healthcare facilities. Outcome measures included health facility infrastructures, access to medicines, and sources of financial support. A total of 34 studies conducted met our inclusion criteria. Health financing and developing health infrastructure were the most reported interventions toward achieving UHC. Our results suggest that strengthening the health system, namely, through health financing, developing, and improving the health infrastructure, can play an important role in reaching UHC in the African context.